The Position of Collective Labor Agreements in Guaranteeing Legal Certainty of the Rights of Outsourced Workers in Indonesia - Safrida (International Journal of Science and Environment (IJSE), 2025)
Collective Labour Agreements (CLA) constitute one of the essential instruments in the Indonesian industrial relations system. Beyond functioning as a product of collective bargaining between employers and trade unions, a CLA also serves as a legal instrument aimed at ensuring legal certainty regarding the rights and obligations of both parties in employment relations. In practice, however, legal protection for outsourced workers remains a significant issue, particularly due to their vulnerable employment position, contractual uncertainty, and limited bargaining power. This study examines the position of Collective Labour Agreements in guaranteeing legal certainty for outsourced workers’ rights in Indonesia. Employing a normative legal research method with statutory, conceptual, and case approaches, this study analyzes relevant legislation, legal doctrines, judicial decisions, and scholarly works concerning industrial relations and outsourcing arrangements. The findings indicate that Collective Labour Agreements possess a strategic position as a source of labour law capable of strengthening legal protection beyond the minimum standards established by legislation. Nevertheless, the effectiveness of such agreements in protecting outsourced workers remains constrained by the absence of explicit clauses, unequal bargaining positions, and inconsistencies in implementation. Therefore, strengthening the substance of Collective Labour Agreements is necessary to ensure greater legal certainty and protection for outsourced workers within the Indonesian industrial relations framework.